1992
DOI: 10.3133/pp1404g
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeologic framework of the northern Atlantic Coastal Plain in parts of North Carolina, Virginia, Maryland, Delaware, New Jersey, and New York

Abstract: The Regional Aquifer-System Analysis (RASA) Program was started in 1978 following a congressional mandate to develop quantitative appraisals of the major groundwater systems of the United States. The RASA Program represents a systematic effort to study a number of the Nation's most important aquifer systems, which in aggregate underlie much of the country and which represent an important component of the Nation's total water supply. In general, the boundaries of these studies are identified by the hydrologic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
1
14
0
1
Order By: Relevance
“…This study focused on wells in the surficial aquifer that consists of unconsolidated sand and gravel and is the uppermost aquifer in the North Atlantic Coastal Plain aquifer system (Trapp, 1992). Average annual temperature is 11° C and average annual precipitation is 1,044 mm (Polsky et al, 2000).…”
Section: Site Descriptionmentioning
confidence: 99%
“…This study focused on wells in the surficial aquifer that consists of unconsolidated sand and gravel and is the uppermost aquifer in the North Atlantic Coastal Plain aquifer system (Trapp, 1992). Average annual temperature is 11° C and average annual precipitation is 1,044 mm (Polsky et al, 2000).…”
Section: Site Descriptionmentioning
confidence: 99%
“…(1) Results of studies of the general geology and hydrology of the study area have been reported by Jordan and Groot (1962), Bonini (1967), Spoljaric (1967), Spoljaric and Woodruff (1970), Owens and others (1970), Pickett (1970), Pickett and Spoljaric (1971), Gushing and others (1973), Woodruff (1981 and1986), Duran (1986), Trapp (1992), and Vroblesky and Fleck (1991).…”
Section: Previous Investigationsmentioning
confidence: 86%
“…The uGW was collected from a public supply well in the Piney Point Aquifer in Southeastern New Jersey. This confined aquifer extends from Virginia through New Jersey, is approximately 2/3 the width of the North Atlantic Coastal Plain, and does not outcrop in either Maryland or New Jersey (Trapp, 1992). Carbon-14 age estimates for samples taken from this aquifer in Maryland are greater than 30,000 yr old (Aeschbach-Hertig et al, 2002).…”
Section: Microscopic Examination Of Surface and Groundwatermentioning
confidence: 98%